Information technologies for decision support systems in regional development management - Prosyankina-Zharova, Tetyana (Kyiv National University of Construction and Architecture, 2025)
The paper is devoted to the current scientific and applied problem – development of information technologies to support decision-making in regional development management. The proposed information technologies are intended for use in state and public administration systems. They can be used separately, but to increase the efficiency of their use, it is proposed to combine them in a single information system for regional development management. The proposed information technologies combine methods of extracting, storing, collecting and processing structured and unstructured data, mathematical modeling, methods of intelligent data analysis, scenario analysis, cognitive modeling, artificial intelligence, geoinformation technologies, information protection tools, etc.The implementation of such a system will improve the quality of governance at the level of regions and communities, will allow optimizing analytical processes on the ground, reduce costs for the digitalization of regions, will contribute to the establishment of feedback between regions and the state and between society and the state.To build and deploy the system, it is proposed to use the Oracle hardware and software platform, which will allow implementing the network-centric concept of the system, solving problems of interoperability and processing large data sets.To implement the analytical component of the system, in addition to Oracle BI, SAS Institute software was used. Thanks to this, a powerful adaptive data processing subsystem was created, a wide range of models can be built. SAS Institute software integrates well with various development environments, including those available in the public domain, which allows you to expand the system by developing your own modules, in particular, using the Python programming language.It is envisaged that the system will be scalable. Taking into account the specifics of the system's purpose, a comprehensive information protection system with confirmed compliance is envisaged.In the future, the system can be expanded by adding new mathematical models and their ensembles, geospatial information processing tools, and artificial intelligence.